1999
DOI: 10.1063/1.371618
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron emission coefficient of a MgO single crystal

Abstract: Influence of duty cycle on the structure and secondary electron emission properties of MgO films deposited by pulsed mid-frequency magnetron sputtering Electron ejection from MgO thin films by low energy noble gas ions: Energy dependence and initial instability of the secondary electron emission coefficient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…The cathode fall voltage is known to be closely related to γ , which was treated theoretically in references [39,44] and evaluated experimentally in this study, using the C12A7 electride. Figure 3 shows the setup used for measuring γ in this study [32][33][34][35][45][46][47][48][49]. It consists of a vacuum chamber, an ion gun and an electrode to collect the emitted electrons.…”
Section: Secondary Electron Emissionmentioning
confidence: 99%
“…The cathode fall voltage is known to be closely related to γ , which was treated theoretically in references [39,44] and evaluated experimentally in this study, using the C12A7 electride. Figure 3 shows the setup used for measuring γ in this study [32][33][34][35][45][46][47][48][49]. It consists of a vacuum chamber, an ion gun and an electrode to collect the emitted electrons.…”
Section: Secondary Electron Emissionmentioning
confidence: 99%
“…The increase of O 2 flow rate results an increase of d. Recently, Choi et al [189] studied the work functions and d coefficients of h1 1 1i, h1 0 0i and h1 1 0i surfaces of MgO and established that the h1 1 1i surface has the lowest work function, corresponding to a maximum kinetic energy of the ejected secondary electrons from the MgO films [190][191][192] and therefore observed a higher d coefficient. In addition, it has been reported that defects in the films could trap the excited secondary electrons leading to a decrease of the amount of the secondary electrons escaping from film surface and therefore to decrease of d. Cheng et al [149] reported that the d coefficient increases with increasing E/P, where E is the applied field and P is the pressure between the cells.…”
Section: Secondary Electron Emission Yieldmentioning
confidence: 99%
“…There have been many experiments and theoretical approaches to find the SEEC of MgO or other protective materials [5][6][7]. However, these experiments or theories present different SEEC values.…”
Section: Ion Angle and Energy Distributionsmentioning
confidence: 99%